Pentraxin 3, TNF-α, and LDL-C Are Associated With Carotid Artery Stenosis in Patients With Ischemic Stroke - Yi, Li; Tang, Jie; Shi, Cuige; Zhang, Tingting; Li, Jing; Guo, Fang; Zhang, Wei (Frontiers in Neurology, 2020)
Background: Carotid artery stenosis (CAS), typically resulting from atherosclerotic progression, is more common than intracranial atherosclerotic disease in patients with cerebrovascular disease. Prior literature has incompletely established the relationship of Pentraxin 3 (PTX3) and CAS complexity and severity. This study aims to more thoroughly evaluate the association of plasma PTX3 levels and the prevalence and severity of CAS in patients with cerebrovascular disease. Methods: 206 patients with ischemic stroke underwent multiphase computerized tomography angiography (CTA) of the head and neck to assess the presence and severity of carotid artery stenosis. Patients were divided into groups with either no carotid artery stenosis (CAS-free) or carotid artery stenosis (CAS). The CAS group was further divided into groups based on the degree of stenosis and the number of involved vessels. The PTX3 and Tumor Necrosis Factor-alpha (TNF-α) concentration were measured by ELISA. Results: Plasma levels of PTX3, TNF-α, and low-density lipoprotein cholesterol (LDL-C) were increased significantly in the CAS group patients versus the CAS-free group (p=0.000, 0.002, 0.002, respectively). Within the CAS group, PTX3, TNF-α, and LDL-C were significantly elevated in stenosis of ≥50% group compared to <50% group (p=0.001, 0.002, 0.049, respectively). The multivariate logistic binary regression analysis revealed that increased age, elevated levels of PTX3, LDL-C, and TNF-α were all independent risk factors for occurrence of carotid stenosis. PTX3 level correlated with the severity of carotid stenosis. Conclusions: High plasma PTX3 levels, TNF-α, and LDL-C are significantly correlated with the prevalence and severity of carotid artery stenosis. PTX3 may be a more powerful predictor for the severity of carotid artery stenosis.